Analisis Kualitas Garam Lokal di Kabupaten Aceh Timur Dengan Berbagai Metode Pengolahan Garam: Analysis of Local Salt Quality in East Aceh Regency with Various Salt Processing Methods (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2024)
Salt is one of the local commodities produced by the people of East Aceh District. This salt is widely utilized as an additive substance in the processing of various commodities, including fish preservation and the production of “asam sunti”. The quality of salt is greatly influenced by the concentration of seawater and their processing method. The purpose of this study was to examine the effect of production salt processing methods on the quality of the salt produced and to compare the results of analysis with SNI for consumption of iodized salt. The method used in this study is a comparative research method, which compares the quality parameters of salt produced by geomembrane (G1), boiling (G2) and a combination both of them (G3). The quality parameters analyzed were water content, NaCl content, iodine content, and water insoluble portion. The results of analysis compared with the standard SNI 3556: 2016 Concerning Iodized Consumable Salt show that the water content in G1, G2, G3 is 0, 7, and 6,4 respectively, the NaCl level in G1, G2, G3 is 120, respectively. 51, 10.98, 12.29, the water insoluble portion in G1, G2, G3 was 2, 4, 2,5 respectively and the iodine content in G1, G2, G3 was 34,65, 42,49, 47,46 respectively, so it can be concluded that geomembrane production method has better salt quality compared to the boiling production method and a combination of the two. NaCl levels and iodine levels produced through the production of geomembranes have reached the established standards SNI 3556:2010 concerning Iodized consumption salt.